DEVELOPING WEBSITE FOR TEACHING SIMULTANEOUS AND CONSECUTIVE INTERPRETING - Atsani Wulansari; Gilang Fadhilia Arvianti (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2023)
The website is needed for the teaching and learning process; furthermore, the website is also an essential element in adding learning material, especially in online learning. In line with that, Rahman et al. (2016) revealed that website-based learning media can be used in the classroom as it can encourage students to do various activities in learning. This research aims to develop and validate the designed website and the material inside it. This study applied Research and Development by Sugiyono, which are (1) Planning; (2) Developing; (3) Validating; (4) Revising. This research involved three expert validators of media and three expert validators of material. In addition, forty-six students in the translation and interpreting class were the respondents in this research. The data were taken from observation, questionnaires distributed to students and expert validators, and interviews. The findings of this study show that the website should be developed based on the students' needs and suggestions. Aside from that, the validation results state that the web is feasible to use with a few revisions.